PSMA-Directed Radioligand Therapy for Metastatic Prostate Cancer - Ellen Heitlinger (healthbook TIMES. Oncology Hematology)
Prostate cancer is the leading cause of total years of life lost due to cancer in men, despite developments in treatment and technology. Improved outcomes and novel therapy concepts, such as theranostics, are urgently needed. A typical example of theranostics, defined as a combination of therapy and diagnostic, is the use of radiolabeled ligands that bind to a specific target on a cancer cell and emit radiation, allowing treatment planning, dosimetry and imaging using positron emission tomography (PET). Some radioligands, such as ^177^Lu-PSMA-617, can also emit β-radiation which leads to apoptosis of tumor cells. At the Swiss Oncology and Hematology Congress (SOHC) 2023, Prof. Dr Wolfgang Fendler from Essen and Prof. Dr Irene Burger from Zurich discussed results from the studies assessing ^177^Lu-PSMA-617 and ^177^Lu-PSMA-other ligands as a treatment for patients with prostate cancer.